090 UK multiple sclerosis register: understanding the gaps between patient outpatient experiences and preferences. Issue 6 (27th May 2022) - Kee, Rachael; Ramsay, Stephen; McKee, Jon; Middleton, Rod; Rodgers, Jeff; Nicholas, Richard; Kennedy, Fiona; Hughes, Stella; McDonnell, Gavin
Abstract : Background: Provision of care to patients with Multiple Sclerosis (MS) is complex and an effective multi- disciplinary team (MDT) approach is needed. We surveyed patients' experiences of ideal care and care actually provided. Methods: We designed a questionnaire to evaluate service provision and expectation in a nationwide cohort of patients from the UK MS Register with subsequent qualitative and quantitative data analysis. Results: 2512 patients responded. 58% attend a specialist MS Clinic. Mean age 56 years, median EDSS 6.0. Of patients with established diagnoses, 48% had RRMS, 35% SPMS, 12% PPMS, 5% undetermined. The biggest reported gaps at clinic were; physiotherapy (reality vs preference) 13% vs 45%, occupational therapy 6% vs 31% and continence advice 6% vs 29%. Clinical course did not influence expectation in these services. Substantial gaps also existed for counselling and dietetics provision. 18% of patients did not report new symptoms/relapses to any healthcare professional. RRMS patients were less likely to be part of this group and PPMS patients more likely, with no difference between genders. Conclusions: This study illustrates a gap between MDT service provision and patient preference at MS/neurology clinics throughout the UK, and across all patient subgroups. A concerning number of patients do not report new symptoms to MS services, particularly PPMS patients. Further resources should be directed towards bridging these care gaps for MS patients. rachael: kee@doctors.org.uk|ABN Bursary 70